Morse Taper Connection Implants Placed in Grafted Sinuses in 65 Patients: A Retrospective Clinical Study with 10 Years of Follow-Up. (7th August 2017) - Mangano, Francesco; Bakaj, Renata; Frezzato, Irene; Frezzato, Alberto; Montini, Sergio; Mangano, Carlo
Abstract : Purpose . To investigate the 10-year survival and complication rates of Morse taper connection implants (MTCIs) placed in grafted sinuses. Methods . This study reports on patients treated with maxillary sinus augmentation (with the lateral window technique (LWT) or the transalveolar osteotomy technique (TOT)) and installed with MTCIs supporting fixed restorations (single crowns (SCs) and fixed partial dentures (FPDs)), in two dental clinics. The outcomes of the study were the 10-year implant survival and complication rates. Results . Sixty-five patients (30 males and 35 females) with a mean age of 62.7 (±10.2) years were installed with 142 MTCIs: 79 fixtures were inserted with the LWT and 63 were placed with the TOT. After ten years, five implants failed, for an overall survival rate of 96.5%. Three implants failed in the LWT group, for a survival rate of 96.3%; two implants failed in the TOT group, for a survival rate of 96.9%. The 10-year incidence of biologic complications was 11.9%. Prosthetic complications were all technical in nature and amounted to 7.6%. Conclusions . MTCIs seem to represent a successful procedure for the prosthetic restoration of the grafted posterior maxilla, in the long term. This study was registered in the ISRCTN registry with numberISRCTN30772506 .